2010
DOI: 10.1093/nar/gkp1222
|View full text |Cite
|
Sign up to set email alerts
|

A truncated DNA-damage-signaling response is activated after DSB formation in the G1 phase of Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, the DNA damage response (DDR) is activated by the spatio-temporal colocalization of Mec1-Ddc2 kinase and the 9-1-1 clamp. In the absence of direct means to monitor Mec1 kinase activation in vivo, activation of the checkpoint kinase Rad53 has been taken as a proxy for DDR activation. Here, we identify serine 378 of the Rad55 recombination protein as a direct target site of Mec1. Rad55-S378 phosphorylation leads to an electrophoretic mobility shift of the protein and acts as a sentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…As a consequence, Mec1 and Rad53 kinases are activated and the DNA damage checkpoint signaling contributes to block cell cycle progression in metaphase. Supporting this model, we did not observe Tid1 phosphorylation after one DSB induced in G1-blocked cells (Figure 2A), in which DSB ends are not efficiently processed and Mec1-signaling is not fully active [22,23]. Moreover, Tid1 phosphorylation decreases both during checkpoint recovery and adaptation, in response to one repairable and irreparable DSB (Figures 2B and 3A).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As a consequence, Mec1 and Rad53 kinases are activated and the DNA damage checkpoint signaling contributes to block cell cycle progression in metaphase. Supporting this model, we did not observe Tid1 phosphorylation after one DSB induced in G1-blocked cells (Figure 2A), in which DSB ends are not efficiently processed and Mec1-signaling is not fully active [22,23]. Moreover, Tid1 phosphorylation decreases both during checkpoint recovery and adaptation, in response to one repairable and irreparable DSB (Figures 2B and 3A).…”
Section: Discussionmentioning
confidence: 63%
“…It is known that one irreparable DSB is processed and activates a full Mec1-dependent checkpoint pathway in G2-blocked cells, but not in G1-blocked cells [22,23], thus we tested Tid1 and Rad53 phosphorylation in cells treated with α-factor or nocodazole to block the cell cycle in G1 or G2 phases, respectively. We found that Tid1 is not phosphorylated after one irreparable DSB induced in G1-blocked cells, while its phosphorylation is accumulated in G2-blocked cells, following the formation of one irreparable DSB and the activation of Rad53 (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Rad55 is phosphorylated in response to DNA damage on multiple residues by Mec1 (serine 378), Rad53 (serine 14), and an unidentified kinase (serines 2, 8) (13, 66, 79). The N-terminal phosphorylation mutant (Rad55-S2,8,14A) displays strong defects in growth and survival in response to the alkylating agent methyl methansulfonate.…”
Section: The Rad51 Filament: a Balance Between Formation And Disruptionmentioning
confidence: 99%
“…To exclude the possibility that mild DNA damage might not be detected by this method, we examined the sensitivity of Rad53 phosphorylation using HO endonuclease, a sequence-specific double-strand nuclease of yeast used in mating type switch. Unlike MMS, the expression of HO endonuclease results in a single DNA double-strand break, which is repaired by the Rad53-mediated DNA repair pathway (32). While Rad53 phosphorylation was clearly induced by HO expression in both wild-type and rad52Δ cells, Rad53 phosphorylation was not detected in rad52Δ cells without HO expression as in wild-type cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%